Hydrogen gas reduces chronic intermittent hypoxia‐induced hypertension by inhibiting sympathetic nerve activity and increasing vasodilator responses via the antioxidation. Issue 3 (27th September 2018) - Guan, Peng; Lin, Xiao‐Meng; Yang, Sheng‐Chang; Guo, Ya‐Jing; Li, Wen‐Ya; Zhao, Ya‐Shuo; Yu, Fu‐Yang; Sun, Zhi‐Min; An, Ji‐Ren; Ji, En‐Sheng
Abstract: Molecular hydrogen is reported to be used medically to ameliorate various systemic pathological conditions. This study aimed to investigate the effect of hydrogen (H2 ) gas on hypertension induced by intermittent hypoxia in rats. The adult rats were exposed to chronic intermittent hypoxia (CIH) 8 hours/day for 5 weeks and/or H 2 gas 2 hours/day. We found that the systolic and diastolic blood pressure (BP) increased significantly in rats exposed to intermittent hypoxia, both of which were markedly attenuated after H treatment. Furthermore, intermittent hypoxia exposure elevated renal sympathetic nerve activity, consistent with plasma norepinephrine. Additionally, H 2 gas significantly improved CIH‐induced abnormal vascular relaxation. Nevertheless, inhalation of H 2 gas alone did not cause such changes. Moreover, H 2 gas‐treated rats exposed to CIH showed a significant reduction in 8‐hydroxy‐2 deoxyguanosine content and increases in superoxide dismutase activity, indicating improved oxidative stress. Taken together, these results indicate that H 2 gas has significant effects on the reduction of BP without any side effects. Mechanistically, inhibition of sympathetic activity and reduction of systemic vascular resistance may participate in this process via the antioxidant activity of H 2 . Abstract : Hydrogen (H2 ) is effective in preventing hypertension with no significant adverse effects via antioxidation. H2 downregulated sympathetic activity in rats with chronic intermittent hypoxia (CIH). H2 reduced the resistance of mesenteric artery in rats with CIH.